DISCLOSING INFORMATION ABOUT OPERATIONAL SEGMENTS - Elvira I. Bakhtigozina (Plekhanov Russian University of Economics, 2017)
Lately the requirements to truthfulness of finance accounting are becoming stricter. Information about operational segments, i. e. separate business components fosters more detail understanding of the company activity. The article discusses specific features of disclosing information about different-profile business components in footnotes to finance accounting. The author puts forward concrete recommendations on distinguishing considerable operational segments in order to show them in accounting. As in practice the majority of questions arise in identification of segments and the level of segment information importance, the character of information disclosed about operational segments the author using a concrete example shows the process of assessing and distinguishing operational segments (by calculating the threshold values, criteria), integration of non-considerable segments taken separately but rather important as a result of consolidation.